Storage Capacity and Palatability of Wafer Complete Ration Based on Sugar Cane Top and Bagasse on Calves - Y Retnani; W Widiarti; I Amiroh; L Herawati; K B Satoto (Media Peternakan, 2009)
Sugar cane top and bagasse represent agricultural by product which is potential as feed. This research was aimed to study of physical characteristics of wafer complete ration containing sugar cane top and bagasse during storage for six weeks. The treatments were alocated in completely randomized factorial design. The treatments as factor A were R0=80% concentrate + 20% native grass; R1=concentrate 80% + 20% bagasse; R2=concentrate 80% + sugar cane top 10% + bagasse 10%; R3=concentrate 80% + 20% sugar cane top. Factor B was storage period i.e., B1=0 week; B2=2 weeks; B3=4 weeks; B4=6 weeks. The result showed that the wafer complete ration contained natural grass, sugar cane top and bagasse did not affect the specific density and water activity, but the water content was the highest (P < 0.01) in ration containing natural grasses. Storage for six weeks affected (P < 0.01) water content, density and specific density, but did not affect water activity. Wafer complete ration palatability containing grass and sugar cane top was more preferred than sugar cane top combined with bagasse or bagasse without combination. Key words: wafer complete ration, sugar cane top, bagasse, storage, calves